Thermophysical properties enhancement of KNO3–NaNO3–NaNO2 mixed with SiO2/MgO nanoparticles - Baiyuan Tian; Chuang Zhu; Manting Gu; Minhao Xu; Wenxuan He (Journal of Science: Advanced Materials and Devices)
This study aims to discover innovative thermal storage materials that fulfill the specifications of concentrated solar power systems. Thermal storage materials based on ternary eutectic (Hitec) with nano-SiO2 and nano-MgO are investigated. Simultaneous thermal analysis and laser flash analysis are used to study the main properties of materials. The results indicate that the inclusion of nano-SiO2 and nano-MgO reduces the melting point while enhancing the latent heat of the base salt. Doping the base salt with 0.3 wt% nano-SiO2 and 0.7 wt% nano-MgO results in molten salt nanocomposites with an average specific heat of 2.16 J/(g⋅K), which is 54.3% higher than that of the base salt. This surpasses the specific heat of the base salt mixed with a single type of nanoparticle. The thermal conductivity of this nanocomposite is increased by 13.13% to 0.836 W/(m⋅K) compared to the base salt. Furthermore, this study demonstrated that the effect of interfacial thermal resistance on specific heat capacity and heat transfer characteristics is the opposite. While the nanoparticles can increase the specific heat capacity of the molten salt, they can also reduce the heat transfer rate within this material.